2021
DOI: 10.1111/jam.15027
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of enteric viruses during a hepatitis outbreak in Detroit MI using wastewater surveillance and metagenomic analysis

Abstract: Aims: This study investigates enteric viruses in wastewater during an outbreak of acute hepatitis caused by hepatitis A virus (HAV) in a large metropolitan area. Emphasis is given to caliciviruses and HAV. Methods and Results: Metagenomic analysis was performed to characterize enteric viruses excreted by the population of Detroit MI, during a hepatitis A outbreak that occurred in 2017 and 2018. Additionally, HAV, norovirus GII, and sapovirus were quantified, using qPCR, in 54 untreated wastewater samples colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“…The utility of WBE has been demonstrated for understanding community circulation of poliovirus 8 , Salmonella 9 , hepatitis A 10 , and enteroviruses 11 , but its use has not widely been a part of disease surveillance outside of polio in endemic regions. The application of WBE to respiratory diseases is relatively new and was prompted by the COVID-19 pandemic, during which it was widely shown that concentrations of SARS-CoV-2 RNA in wastewater correlate to reported COVID-19 incidence rates during periods of widely accessible clinical testing 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The utility of WBE has been demonstrated for understanding community circulation of poliovirus 8 , Salmonella 9 , hepatitis A 10 , and enteroviruses 11 , but its use has not widely been a part of disease surveillance outside of polio in endemic regions. The application of WBE to respiratory diseases is relatively new and was prompted by the COVID-19 pandemic, during which it was widely shown that concentrations of SARS-CoV-2 RNA in wastewater correlate to reported COVID-19 incidence rates during periods of widely accessible clinical testing 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Enveloped viruses (viruses with a lipid envelope that include influenza viruses, coronaviruses, and parainfluenza viruses) are usually less stable in the environment than non-enveloped viruses (without a lipid envelope, including enteroviruses, noroviruses, and adenoviruses). Noroviruses and adenoviruses can survive up to months in the environment (Kotwal & Cannon 2014) and have frequently been detected in wastewater and surface waters (Lago et al 2003;La Rosa et al 2010;Rajko-Nenow et al 2013;Guillois et al 2016;Farkas et al 2018;Falman et al 2019;Mancini et al 2019;McCall et al 2021). However, very limited information currently exists on the persistence of the genetic material of enveloped viruses in the environment, especially in wastewater.…”
Section: Impacts Of Wastewater Environments On Viral Detectionmentioning
confidence: 99%
“…WBE has been used to measure the prevalence of several other human viruses at the population level including measles (Benschop et al, 2017), enteroviruses (Brinkman et al, 2017), hepatitis A (Hellmér et al, 2014;McCall et al, 2021), hepatitis E (Alfonsi et al, 2018), norovirus (Hellmér et al, 2014;Lu et al, 2021), and more recently, extensive analysis of SARS-CoV-2, which will be discussed in the next section. Some of these studies have used WBE as an early indicator of outbreaks (Hellmér et al, 2014), or to indicate trends in the prevalence of difference viruses (Brinkman et al, 2017).…”
Section: Estimation Of Infectious Disease Prevalencementioning
confidence: 99%